Analisa Komponen Bina Marga Untuk Perhitungan Tebal Perkerasan Jalan Kepatihan-Warujayeng Kabupaten Nganjuk - Wibisono, R. Endro; Yuana, Buger Wijaya; Susanti, Anita (Universitas Dr. Soetomo, 2021)
Pavement is one of the elements of highway construction which is very important in the context of smooth land transportation so as to provide security and comfort for its users, so that the pavement needs to be planned properly based on the standards and planning criteria that apply in Indonesia. However, there are still indequate road pavements in various parts of Indonesia. One of them is on the Kepatihan-Warujayeng road, Nganjuk Regency. This road is a connecting road between Nganjuk Regency and Jombang Regency. This study aims to analyze the pavement thickness planning for the Kepatihan-Warujayeng road, Nganjuk Regency. Research analysis using the method of Bina Marga 1979, AASHTO 1993. With a plan age of 10 years on the Kepatihan-Warujayeng road. Based on the results of calculations and analysis, it was found that the type of flexible pavement was to repair the damage. The first calculation of Jalan Kepatihan Warujayeng with pavement thickness of Laston AC 13cm, Base 27cm, and Sub base 21cm and the second calculation of Jalan Kepatihan Warujayeng obtained results with pavement thickness Laston AC 11cm, Base 25cm, and sub base using a minimum pavement thickness of 20 cm